Potential effect of anti‐inflammatory drug use on PSA kinetics and subsequent prostate cancer diagnosis: Risk stratification in black and white men with benign prostate biopsy. Issue 10 (2nd May 2019) - Kryvenko, Oleksandr N.; Wang, Yun; Sadasivan, Sudha; Gupta, Nilesh S.; Rogers, Craig; Bobbitt, Kevin; Chitale, Dhananjay A.; Rundle, Andrew; Tang, Deliang; Rybicki, Benjamin A.
Abstract: Background: Rising prostate‐specific antigen (PSA) levels are associated with both increased risk of prostate cancer and prostatic inflammation. The confounding effects of inflammation on the utility of PSA kinetics to predict prostate cancer may be partially mitigated by anti‐inflammatory drug use. We investigated the influence of anti‐inflammatory drug use on the association of PSA kinetics with prostate cancer risk. Methods: We studied 488 prostate cancer case‐control pairs (290 white, 198 African American (AA)) nested in a retrospective cohort of men with a benign prostate biopsy. A series of multivariable models estimated prostate cancer risk associated with PSA velocity (PSAV) at different levels of anti‐inflammatory drug use while adjusting for the presence of both clinical and histologic prostatitis. Results: In men with one, two, or three or more courses of anti‐inflammatory drug use, for each ng/mL/year increase in PSAV, prostate cancer risk increased 1.21‐fold, 1.83‐fold, and 1.97‐fold, respectively ( P  < 0.0001). In controls with histologic prostatitis, anti‐inflammatory drug use was associated with a significantly lower PSAV ( P  < 0.0001). This association was not observed in men with histologic prostatitis who were subsequently diagnosed with prostate cancer. A positive interaction between anti‐inflammatory drug use and PSAV‐associated prostate cancer risk was only observed in AA men, as well as a strong positive association between any anti‐inflammatory drug use and clinical prostatitis ( P  = 0.004). Conclusions: In men with benign prostate biopsy, accounting for the presence of histologic prostatitis and anti‐inflammatory drug use, particularly in AA men, may help distinguish between men with rising PSA because of prostatitis vs undiagnosed cancer.